Strengthening of Damaged Masonry Walls Using Engineered Cementitious Composites: Experimental and Numerical Analysis - S. M. Renuka; I. P. Mervin Sanjith (Advances in Civil Engineering)
Engineered cementitious composites (ECC) are special types of high-tensile and high-ductility concrete that are designed using a micromechanics approach, with a tensile strain capability of more than 3%. Due to their higher strain hardening capacity, ECC can be applied as a strengthening material on structural walls, which improves the structural strength and inelastic deformation capacity. This study presents an experimental and numerical analysis of brick masonry wall strengthened by traditional mortar, ECC, and ECC with 40% fly ash (FAECC) subjected to uniaxial compression. The tests, such as compressive strength, indirect tensile strength, and bond strength, were conducted. Based on the experimental results, a numerical model is developed, and a failure prediction for the existing masonry structure is made. The compressive strength of ECC is observed to be higher than normal mortar and FAECC whereas the indirect tensile strength of both ECC and FAECC was almost similar, which is higher than that of normal mortar. The bond strength of ECC and FAECC is found to be 70% higher than that of normal mortar. It is evident that brick masonry units strengthened by ECC have a higher compressive strength than masonry units strengthened by conventional mortar and FAECC. It also controls crack development and spalling of masonry units. Then, a micromodelling along with CDP model is made in Abaqus/CAE software and an excellent correlation between experimental and numerical results was noted. The suggested models were shown to be capable of predicting the common behaviour of masonry units.